2004
DOI: 10.1086/425075
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Increases in CD4 Cell Counts of HIV‐Positive Persons Receiving Long‐Term Highly Active Antiretroviral Therapy

Abstract: These findings emphasize the importance of maintaining virological suppression and suggest other factors that influence long-term CD4 cell response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
124
3
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(158 citation statements)
references
References 37 publications
28
124
3
3
Order By: Relevance
“…This is in contrast to another study which reported that treatment outcomes in adult HIV naïve patients were not based on the baseline CD4 cell count (Kyaw et al, 2013). Specifically in terms of gender, some studies dissociated sex as a risk factor of immunological failure (Lawn et al, 2006;Smith et al, 2004) which is in tandem with our results. It was observed in this study that the patients appeared to have had late enrolment into HIV care with 70.2% of the patients having absolute CD4 count of ≤ 200 cells/µl (median CD4 <140.0 cells/µl) at ART initiation.…”
Section: Discussionsupporting
confidence: 87%
“…This is in contrast to another study which reported that treatment outcomes in adult HIV naïve patients were not based on the baseline CD4 cell count (Kyaw et al, 2013). Specifically in terms of gender, some studies dissociated sex as a risk factor of immunological failure (Lawn et al, 2006;Smith et al, 2004) which is in tandem with our results. It was observed in this study that the patients appeared to have had late enrolment into HIV care with 70.2% of the patients having absolute CD4 count of ≤ 200 cells/µl (median CD4 <140.0 cells/µl) at ART initiation.…”
Section: Discussionsupporting
confidence: 87%
“…19 Patients initiating HAART experience substantial increases in CD4 cell counts regardless of the CD4 cell count at initiation, with slightly greater average increases in patients with low CD4 cell counts at initiation. [20][21][22] In the Swiss HIV Cohort Study 21,23 and a Spanish cohort, 24 the likelihood that patients achieved a CD4 count >500 cells/µL up to 5 years after starting HAART was inversely associated with baseline CD4 cell count, and in gay men enrolled in the Multicenter AIDS Cohort Study, the CD4 cell count increased during the first 2 years of therapy but reached a plateau thereafter. 25 Poorer outcomes in patients starting HAART at low CD4 cell counts, compared with those starting at higher CD4 cell counts, are therefore likely to be explained by the lower CD4 cell counts experienced by these patients after initiation of HAART.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, migrants were not found to have an impaired response to HAART neither in Denmark [23] nor in London [24]. These two latter studies included individuals regardless of history of antiretroviral treatment prior to HAART initiation; since history of pre-HAART treatment, a strong predictor of response to HAART, is likely to be distributed differentially among migrants and non migrants, differences may have been underestimated in these studies.…”
Section: Differences In Treatment Failure Rates Across Subgroupsmentioning
confidence: 97%